A New Approach to Estimate the Complex Relative Permittivity of Materials Based on Free-Space Reflection Method - Nguyen, L. C.; Ho, M. C.; Le, T.-H. (Advanced Electromagnetics, 2020)
A microwave free-space reflection method for determining the complex permittivity of planar materials is demonstrated. Improved the MUltiple SIgnal Classification (MUSIC) algorithm to estimate the complex relative permittivity of material based on the reflection coefficients measurement of a metal-backed material sample placed in a free-space with the thickness of the samples is the much greater time the wavelength. The measurement system consists of a pyramidal horn antenna operating at X-band and a metal-backed sample placed in a free-space. From the measured values of the reflection coefficients through a known thickness of a planar slab of the material sample, the complex relative permittivity of the material samples is estimated by the proposed algorithm without determining an integer time the wavelength in the sample under test. The proposed algorithm is verified with different thickness material samples at X-band. The estimation results show that the complex relative permittivity of material samples is accurately when thickness changes.